The Effect of Arabic Literacy Program and Learning Motivation on Arabic Language Learning Outcomes - Retisfa Khairanis; Munirul Abidin; Sulthan Al Aziz (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
This study investigates the influence of an Arabic literacy program and learning motivation on students' Arabic learning outcomes at SMP IT Al Amin Padang. The persistent issue of low Arabic achievement highlights the urgency of exploring strategies integrating language literacy with motivational factors. Prior research has often examined these variables in isolation; however, studies that analyze their combined impact, particularly within Arabic language education, are still limited. This research addresses that gap by assessing how both variables jointly affect student performance. Employing a quantitative correlational approach, the study was conducted on 30 students selected through stratified random sampling. Data were gathered using a validated Likert-scale questionnaire to evaluate students' perceptions of the literacy program and their motivation, while academic records were used to assess Arabic learning outcomes. Data analysis included tests of validity and reliability, normality checks, and Pearson correlation analysis. Findings reveal a significant correlation between the literacy program, learning motivation, and student outcomes, with a coefficient of determination of 75.2%. The results suggest integrating literacy initiatives and motivational support can significantly improve Arabic learning. This study offers valuable insights for developing more effective Arabic language teaching strategies at the secondary education level.